Chemometric Analysis of Water Quality Parameters of Dindigul District- A Seasonal Variation Study - Karthikeyan M.; Elango K. P. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The seasonal variations of water quality parameters of 10 blocks of Dindigul districts were discussed in this study, the ground water quality data for 10 physical and chemical parameters collected from ten blocks of Dindigul district were analysed using PCA and the fluoride endemic regions in two blocks were represented using GIS mapping techniques.